Visualisation of the evolution of perforations in oil-based emulsion sheets formed by flat-fan spray nozzles. (July 2021) - Gong, Chen; Li, Dongyang; Kang, Can; Wang, Yuli
Abstract : Oil-based emulsions are been widely used to apply agricultural sprays and they are often delivered through flat-fan spray nozzles mounted on booms. Perforations are one of the typical structures of found during the atomisation of oil-based emulsions, and they are investigated here using visualisation. The generation, development and coalescence of perforations in an expanding liquid sheet are comprehensively studied. The results support the existence of two perforation-generation mechanisms, namely puncture and tear mechanisms. The tear mechanism depends on the thickness modulation of spray sheet caused by surface disturbances. The perforations that are produced by the tear mechanism are widely distributed and are large in number compared with those associated with the puncture mechanism. The increase of the area of perforation exhibits firstly an acceleration followed by a deceleration. The former is ascribed to the effects of surface tension and the expansion of the spray sheet in a spanwise direction, whilst the latter is related to the interaction between perforations. After perforations are formed, the evolution of the area of the perforation is insensitive to the generation mechanism. Generally, the coalescence of two perforations gives rise to one ligament; however, it is demonstrated that multiple ligaments can be produced if the momentums of the perforations are great enough. Highlights: Evolution of perforations of oil-based emulsion spray is quantitatively described. Two mechanisms of perforation generation are proposed and compared. Effect of generation mode on subsequent development of perforation is studied. An improved model for the growth of perforation area is investigated. Patterns of perforations coalescence are revealed and associated with momentum.